Self-Directed Learning for Learner Autonomy: Teachers’ and Students’ Perceptions - Gharti, Luk (Journal of NELTA Gandaki, 2019)
The research entitled Self-directed Learning for Learner Autonomy: Perceptions of Teachers and Students was carried out to explore the perceptions about Self Directed Learning (SDL) for Learner Autonomy (LA) and analyze the roles of teachers to engage students in SDL. Considering the objectives, the primary data was collected from five master level English Language Teaching (ELT) teachers and three groups of master level students from Pokhara, Kaski. The purposive non-random sampling procedure was used to select the participants. The study was conducted using in-depth interview and Focused Group Discussion (FGD) tools to collect data. The obtained data from the respondents were analyzed and interpreted using analytical and interpretative procedure. It is a new approach in language teaching and learning in Nepalese context though it has been practicing since earlier. The finding shows that all the respondents have positive perceptions and its great contribution for developing LA. SDL helps learners to achieve better achievement and effective learning. It helps teachers to find the necessary changes and increases motivation to the learners to learn. But because of student’s unawareness, time constraint, no inspirations of institutions, student’s false assumptions, lack of insight knowledge about SDL, etc are creating the challenges in its proper application. In the study, the teachers’ roles are facilitator, helper, and resource provider by creating different situation, encouraging, orientating, inspiring, using Information Communication Technology (ICT) and using multimodality in the classroom.